Pilot Study: Nutritional and Preclinical Safety Investigation of Fermented Hispidin-Enriched Sanghuangporus sanghuang Mycelia: A Promising Functional Food Material to Improve Sleep - Li, I-Chen; Chang, Fang-Chia; Kuo, Ching-Chuan; Chu, Hsin-Tung; Li, Tsung-Ju; Chen, Chin-Chu (Frontiers in Nutrition, 2022)
Sleep disturbances have been the hallmark of the recent coronavirus disease 2019 pandemic. Studies have shown that once sleep is disrupted, it can lead to psychological and physical health issues which can, in turn, disrupt circadian rhythm and induce further sleep disruption. As consumers are trying to establish healthy routines, nutritional and preclinical safety investigation of fermented hispidin-enriched Sanghuangporus sanghuang mycelia (GKSS) as a novel food material for spontaneous sleep in Sprague-Dawley rats is conducted for the first time. Results showed that the nutritional analysis of GKSS including moisture, ash, crude lipid, crude protein, carbohydrate, and energy were found to be 2.4±0.3%, 8.0±2.5%, 1.7±0.3%, 22.9±1.2%, 65.1±3.1%, and 367.1±10.2 kcal/100 g respectively. In the 28-day repeated-dose oral toxicity study, only Sprague-Dawley male rats receiving 5 g/kg showed a slight decrease in feed consumption at week 3, but no associated clinical signs of toxicity or significant weight loss were observed. Although a significant reduction of the platelet count was found in mid- and high-dose GKSS treated male groups, such changes were noted to be within the normal range and were not correlated with relative spleen weight changes. Hence, the no observed adverse effect level (NOAEL) of GKSS was identified to be higher than 5 g/kg in rats. After the safety of GKSS is confirmed, the sleep-promoting effect of GKSS ethanolic extract enriched with hispidin was further assessed. Despite 75 mg/kg of GKSS ethanolic extract does not affect wakefulness, rapid eye movement (REM) sleep and non-REM (NREM) sleep, GKSS ethanolic extract at 150 mg/kg significantly decreased wakefulness and enhanced NREM and REM sleep. Interestingly, such effects seem to be mediated through anti-inflammatory activities via NF-E2-related factor-2 (Nrf2) signaling pathway. Taken together, these findings provide the preliminary evidence to support the claims suggesting that GKSS contained useful phytochemical hispidin could be considered as safe to use as a functional food agent or nutraceutical for relieving sleep problems mediated by Nrf2 pathway, which the results are useful for future clinical pilot study.